The impact of battery electric vehicles on vehicle purchase and driving behavior in Norway. (January 2018) - Bauer, Gordon
Highlights: Several thousand online survey responses collected from new car buyers in Norway. Buyers of battery electric vehicles are less likely to sell off an older car. Temporal and spatial variation in the BEV and ICEV car markets confirm this result. Subsidizing battery electric vehicles may lead to increased vehicle ownership. Policy recommendations include replacing subsidies with trade-in rebates. Abstract: Battery electric vehicles (BEVs) represent a promising solution to carbon emissions within the transportation sector, but relatively little is known about how limited-range vehicles will change consumer behavior. This study evaluates the impact of large-scale introduction of BEVs on the new car market in Norway, and seeks to determine whether BEVs lead to an increase in household vehicle ownership. Analysis of online survey responses from 4405 new car owners suggests that BEVs lead to an increase in household vehicle ownership of approximately 15–20%. We arrive at this finding using three independent methods: logistic regression of the likelihood of replacing a vehicle on vehicle type, analysis of correlation between the rate of vehicle replacement and BEV market share across municipalities, and linear regression of changes in total new car sales on changes in BEV sales across counties and years. Survey responses on driving habits also suggest that BEV purchases lead to a moderate increase in vehicle miles traveled. These results suggest that real-world emissions savings may be somewhat less than those predicted by life-cycle analysis. Policy recommendations include focusing incentives for BEVs on those bought as replacements for a conventional vehicle.